The Warsaw Ghetto Workshops: Perspectives of Space and Time in Emanuel Ringelblum and Reuven Ben Shem’s Diaries - NIZAN, Victoria (Studia Universitatis Babeș-Bolyai Historia, 2021)
In this paper, I analyze the notion of time and space in the small factories of the Warsaw Ghetto, commonly known as shops, through a close reading of the diaries written in the Ghetto by Emanuel Ringelblum and Reuven Feldschu Ben Shem. In the Warsaw Ghetto of July 22, 1942, there were but two options for Jews: being deported to Treblinka or "postponing" the death sentence by becoming a shop worker. As long as one worked in a shop, one's life ー and only one's life, not his family's ー was spared for a while. The authors of the diaries who will be presented, both worked in the shops, and in their writings, they exposed how space and time became significant oppressing factors. As I will show, every familiar perception was challenged in this space of an imposed slave-like existence. Rezumat: În această lucrare, analizez noţiunea de timp şi spaţiu în micile fabrici din ghetoul din Varşovia, cunoscute în mod obişnuit ca magazine, printr-o citire atentă a jurnalelor scrise în ghetou de Emanuel Ringelblum şi Reuven Feldschu Ben Shem. În Ghetoul din Varşovia, în 22 iulie 1942, nu existau decât două variante pentru evrei: să fie deportaţi la Treblinka sau „amânarea” condamnării la moarte devenind muncitori în magazin. Atâta timp cât cineva a lucrat într-un magazin, viaţa cuiva ー şi numai viaţa cuiva, nu a întregii sale familii ー era cruţată pentru o vreme. Autorii jurnalelor care vor fi prezentate au lucrat în magazine şi în scrierile lor au expus modul în care spaţiul şi timpul au devenit factori opresivi semnificativi. După cum voi arăta, fiecare percepţie familiară a fost contestată în acest spaţiu al existenţei impuse asemănătoare sclavilor. Cuvinte cheie: evrei, al Doilea Război Mondial, ghetoul din Varşovia, Treblinka.